Substrates and organic sources for Physalis peruviana L. seedling production (2020)
The objective was to determine the effect of commercial substrates and organic sources on the production of cape gooseberry seedlings (Physalis peruviana L.). The design was completely randomized with a 2×3 factorial scheme using two commercial substrates (Carolina®, Bioplant®) and three organic sources (control, vermicompost enriched with yoorin thermophosphate and poultry manure) for seedling production. Adding poultry manure to commercial substrates negatively affects precocity and emergence. Carolina® is a suitable substrate for cape gooseberry seedling production without supplements using organic sources. Bioplant® behaves more like an emergence conditioner, requiring supplementation with organic sources (preferably vermicompost). Seedlings that are suitable for transplant can be obtained at 47 days after sowing.